Mobile stroke units services in Germany: a cost-effectiveness modeling perspective on catchment zones, operating modes, and staffing - Rink, Johann; Szabo, Kristina; Hoyer, Carolin; Saver, Jeffrey L.; Nour, May; Audebert, Heinrich J.; Kunz, Wolfgang G.; Froelich, Matthias F.; Heinzl, Armin; Tschalzev, Andrej; Hoffmann, Jens; Schönberg, Stefan; et al. (European journal of neurology, 2025)
Background and Purpose Investigating the cost-effectiveness of future mobile stroke unit (MSU) services with respect to local idiosyncrasies is essential for enabling large-scale implementation of MSU services. The aim of this study was to assess the cost-effectiveness for varying urban German settings and modes of operation. Methods Costs of different operating times together with different personnel configurations were simulated. Different possible catchment zones, ischemic stroke incidence, circadian distribution, rates of alternative diagnoses, as well as missed cases were incorporated to model case coverage and patient numbers. Based on internationally reported clinical outcomes of MSUs, a 5-year Markov model was applied to analyze the cost-effectiveness for the different program setups. Results Compared with standard stroke care, MSUs achieved an additional 0.06 quality-adjusted life years (QALYs) over a 5-year time horizon. Assuming a catchment zone of 750,000 inhabitants and 8 h/7 day operation resulted in an incremental cost-effectiveness ratio (ICER) of €37,182 per QALY from a societal perspective and €45,104 per QALY from a healthcare perspective. Lower ICERs were possible when coverage was expanded to 16 h service on 7 days per week and larger populations. Sensitivity analyses revealed that missing ischemic strokes significantly deteriorated economic performance of MSU. Conclusions Major determinants of cost-effectiveness should be addressed when setting up novel MSU programs. Catchment zones of more than 500,000-700,000 inhabitants and operating times of at least 12-16 h per day, 7 days per week could enable the most cost-effective MSU services in the German healthcare system.
Erstmals veröffentlicht: 06. November 2024
Gesehen am 31.03.2025